How do the poor live? an analysis of the lived experiences of women engaging in microfinance. - Cahilig, Joniel H. (2016.)
Poverty is a universal phenomenon that is well-researched but most of these researches focused on its economic perspective. This research was designed to fulfil the need to study poverty, particularly poor women engaging in microfinance. It tried to examine the psychological aspect of poverty by using Interpretative Phenomenological Analysis (IPA) as the theoretical framework. Data were gathered from six respondents through in-depth interviews and were analyzed using thematic analysis. Three themes emerged from the interviews which explained the lived experiences of the poor women while engaging in microfinance. The first theme talked about the different struggles they went through, like having insufficient daily budgets. The second theme included positive experiences which were mainly caused by their interpersonal relationships. The last theme revolved around their experiences, their perceptions and attitude involving microfinance. Findings showed that interpersonal relationships played a main part on the lived experiences of poor women. It was also found that microfinance have negative psychological effects on its beneficiaries. The women became too dependent to microfinance that it became part of their lifestyle. Also, there is an issue of responsibility such that the beneficiaries do not take the microfinance seriously when it comes to paying back loans.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Microfinance; Women -- Poor; Poverty